1992
DOI: 10.1111/j.1476-5381.1992.tb14299.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the contractile effects of endothelin‐1 and sarafotoxin S6b in goat isolated cerebral arteries

Abstract: 1 The effects of endothelium-derived endothelin-1 and snake venom-derived sarafotoxin S6b, peptides with striking structural and functional similarities, were examined and compared in isolated middle cerebral arteries of goats. 2 Endothelin-l and sarafotoxin S6b contracted cerebral arteries in a concentration-dependent manner.The potency of endothelin-l (EC50 = 4.9 (3.9-6.2) x 10-IOM) was about ten times higher than that of sarafotoxin S6b (EC50 = 5.5 (4.4-6.9) x 10-9 M). The tension returned to basal values a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…A similar differentiation of ETA receptor subtypes has been proposed for endothelin-land endothelin-3-induced contractions in rat thoracic aorta (Sumner et al, 1992). In a previous report (Salom et al, 1992) we have shown that the nature of the extracellular Ca2+ source mobilized by endothelin-1 and sarafotoxin S6b in goat cerebral arteries is also different since endothelin-1 depends on free extracellular Ca2+ and sarafotoxin S6b depends on externally membrane-bound Ca2 . The Ca2+ source could be related to the receptor subtype involved in the response to each of the peptides.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…A similar differentiation of ETA receptor subtypes has been proposed for endothelin-land endothelin-3-induced contractions in rat thoracic aorta (Sumner et al, 1992). In a previous report (Salom et al, 1992) we have shown that the nature of the extracellular Ca2+ source mobilized by endothelin-1 and sarafotoxin S6b in goat cerebral arteries is also different since endothelin-1 depends on free extracellular Ca2+ and sarafotoxin S6b depends on externally membrane-bound Ca2 . The Ca2+ source could be related to the receptor subtype involved in the response to each of the peptides.…”
Section: Discussionsupporting
confidence: 79%
“…We have previously reported the vasoconstrictor effects of endothelin-1 on the cerebrovascular bed of the goat (Salom et al, 1991) and compared them with those of sarafotoxin S6b (Salom et al, 1992). In the present study we have examined the agonist potency of endothelin isopeptides (endothelin-1, endothelin-2 and endothelin-3) and used the selective ETA-receptor antagonist, to …”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation